Implementation Of the Learning Curriculum at Surya Buana High School in Malang - Rizki, Astika Eva; Izati, Devina Nur; Handini, Diah Sri; Arum, Dora Sekar; Aulia, Erend Meiva; Andini, Indri Arifianisa (Universitas Negeri Malang, 2024)
This research aims to: (1) knowing the curriculum structure at SMA Surya Buana Malang; (2) describing the implementation of Curriculum 2013, independent curriculum and portotype curriculum at SMA Surya Buana Malang; (3) identifying factors that influence the implementation of Curriculum 2013; (4) analysing the implementation of technology in the learning process of SMA Surya Buana Malang. This research uses descriptive skinative method. The research was conducted with field research data collection and aims to find out variables, either one variable or more. The results showed that: (1) SMA Surya Buana Malang is one of the private high schools that uses three curricula used for the learning process, namely the 2013 curriculum and the independent curriculum, as well as the BTQ Tahfidz curriculum which is the curriculum of the school itself. (2) The learning process at SMA Surya Buana has been carried out in accordance with the curriculum based on the education office and the school's own curriculum. (3) SMA Su